Guideline-based bismuth quadruple therapy for helicobacter pylori infection in China: A systematic review and network meta-analysis - Jiali Wei; Zehao Zheng; Xin Wang; Boyi Jia; Mingyao Sun; Jiayi Wang; Qin Wan; Mei Han; Yue Qiu (PLoS ONE, 2025)
Background Currently, quadruple therapy is unanimously recommended as the current first-line treatment option for Helicobacter pylori (H. Pylori) eradication. However, the drug composition of quadruple therapy is very complex, and the efficacy and safety between them is not clear. Aims To compare the efficacy and safety of H. Pylori eradication regimens, which were recommended by the Fifth Consensus of China, by network meta-analysis. Methods Literature databases were used to retrieve clinical randomized controlled trials of H. Pylori eradication. Network meta-analysis was performed using BUGSnet and meta package of R software, using OR values as effect size, and SUCRA was used to rank the efficacy of interventions under each outcome. Results A total of 55 studies and 130 arms were included. The NMA analysis found that the top regimen in term of eradication rate outcome was: Rabeprazole +  Bismuth +  Furazolidone +  Tetracycline (SUCRA, 97.5). In terms of safety outcomes: Lansoprazole +  Bismuth +  Amoxycillin +  Clarithromycin (SUCRA, 91.97). Conclusions The bismuth quadruple therapies recommended by the guidelines for the treatment of H. Pylori have good performance in terms of four-week eradication rate and safety outcome indicators, and due to the different resistance of antibiotics in different regional populations, rational use of drugs should be combined with local conditions.